(untitled) (Research, Society and Development, 2022)
On March 11, 2020, the World Health Organization (WHO) recognized COVID-19, a disease caused by the new coronavirus variant (SARS-CoV-2), as a pandemic. This scenario brought a challenge hitherto unexperienced by health services, overloading different categories of workers, in particular nursing professionals. Therefore, this study aims to identify the health promotion actions implemented to nursing workers during the COVID-19 pandemic. The study is an integrative literature review and the search was made based on the analysis of the Virtual Health Library (BVS), EMBASE, SCOPUS and Web of Science databases. The results were analyzed according to the interventions applied. It was observed that within the selected studies there were different interventions focused on promoting the health of nursing workers. The interventions were auriculotherapy, skin product supply and telephone calls. The studies show the benefits of health promotion actions for health workers, especially nursing workers during the COVID 19 pandemic. The actions carried out were aimed at the dermatological and mental health of professionals.